Is the figure-8 fatigue protocol a suitable tool to investigate shoulder muscle fatigue in wheelchair users with spinal cord injury? - Ursina Minder; Ursina Arnet; Erich Müller; Michael Boninger; Franziska Bossuyt (Current Issues in Sport Science, 2023)
Introduction